2010
DOI: 10.1007/s00198-010-1205-6
|View full text |Cite
|
Sign up to set email alerts
|

Age, cohort and period effects on hip fracture incidence: analysis and predictions from New Zealand data 1974-2007

Abstract: The effect of population aging on FNF incidence is predictable because projections are based on an existing population. The increasing health and improvement in measures of physical status of older people through the last century, explain the decline in FNF incidence in later cohorts. The steady increase in period effect may be due to increased survival of the very frail. This burden of illness resulting from FNFs must be addressed by population based, research proven approaches to fall and fracture prevention. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 29 publications
5
35
1
1
Order By: Relevance
“…The stable rates of hip fracture amongst women that we observed in the present study are consistent with many other studies of populations in the developed world, some of which have even documented a decline in age-and sex-adjusted rates [1]. Thus studies in USA [7], Canada [8], Austria [28], France [29], Australia [30] and New Zealand [31] have demonstrated declining age-and sex-specific rates of hip fracture over recent decades, often following an increase in rates in the decades prior. In the UK, a plateau in rates of age-adjusted hospital admission for hip fracture [32] was observed over the years 1989 to 1998.…”
Section: Discussionsupporting
confidence: 81%
“…The stable rates of hip fracture amongst women that we observed in the present study are consistent with many other studies of populations in the developed world, some of which have even documented a decline in age-and sex-adjusted rates [1]. Thus studies in USA [7], Canada [8], Austria [28], France [29], Australia [30] and New Zealand [31] have demonstrated declining age-and sex-specific rates of hip fracture over recent decades, often following an increase in rates in the decades prior. In the UK, a plateau in rates of age-adjusted hospital admission for hip fracture [32] was observed over the years 1989 to 1998.…”
Section: Discussionsupporting
confidence: 81%
“…(6,8) Langley and colleagues have observed as in our study that later cohorts have lower risk of hip fracture, but in contrast to our study, the period effects showed a steady increase in risk. (7) These authors explain the decline observed in later cohorts by increasing health and improvement in physical status of older people since the last century and explain the steady increase observed in period effect by an increased survival in very frail individuals. Moreover, a recent study in Switzerland showed that the decrease observed in women was attributed to a decrease in the incidence of hip fracture among institution-dwelling elderly women.…”
Section: Discussionmentioning
confidence: 96%
“…(1)(2)(3)(4)(5) However, few studies have attempted to assess if these declining rates can be attributed to changes occurring over a specific calendar period (period effect) or to changes affecting individuals born at a specific time (cohort effect). (6)(7)(8)(9) Period effects reflect changes occurring at a specific time and affect all individuals regardless of age. For example, the application of a new diagnostic technique or treatment for osteoporosis in a population might lead to a decrease in hip fracture rates explained by a period effect.…”
mentioning
confidence: 99%
“…Life expectancy has increased in China (23) and increased rates of hip fracture might reflect improved medical care resulting in longer survival of frail elders who are at increased risk of hip fractures. (24) However, paradoxically, studies indicate that the health status of elderly in China improved between 1990 and 2002. (23) The increased risk was also greater for women than men, now more closely resembling the greater ratio of women to men observed in Western countries; the reason for this pattern of change is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Our data derive from two surveys and, therefore, we are unable to determine how much of the change is because of a cohort effect: decreases in rates in successive cohorts or decreases because of changes in conditions between the two periods of time. (24) Assuming no changes in the age-specific incidence of hip fractures around the world, Cooper (2) estimated that 51% of the world's hip fractures would occur in Asia by 2050. However, the age-specific rates of hip fracture are decreasing in northern Europe and North America.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%